Chemical modeling of FU Ori protoplanetary disks. Issue Volume 14:Issue S345(2019) (August 2018) - Molyarova, Tamara; Akimkin, Vitaly; Semenov, Dmitry; Ábrahám, Péter; Henning, Thomas; Kóspál, Ágnes; Vorobyov, Eduard; Wiebe, Dmitri
Abstract: Luminosity outbursts of the FU Ori type stars, which have a magnitude of ∼ 100 L ⊙ and last for decades, may affect chemical composition of the surrounding protoplanetary disk. Using astrochemical modelling we analyse the changes induced by the outburst and search for species sensitive to the luminosity rise. Some changes in the disk molecular composition appear not only during the outburst itself but can also retain for decades after the end of the outburst. We analyse main chemical processes responsible for these effects and assess timescales at which chemically inert species return to the pre-outburst abundances.